(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Consumers’ use of social networking sites has skyrocketed in the contemporary period, and their activities on these sites have far-reaching consequences. Several social networking websites have an impact on buying decisions. Facebook, Twitter, Instagram, YouTube, etc., all have many features that influence and entice large audiences. Today’s consumers increasingly rely on social media to inform their purchasing choices. Marketing via social media platforms is crucial, and it is one of the most effective strategies now available in advertising. Every company owner wants to maximize profits, and they know this is possible through numerous marketing tools and tactics. The study’s primary objective is to investigate the predicted links between different social media marketing operations, customer actions, and consumer behavior, focusing on the latter among heavy social media users.